RESEPSI PEMBACA NOVEL TERPOPULER DI APLIKASI FIZZO “DINIKAHI GUS DINGIN” PENULIS HELLO CUTIE - Apriliana, Elisa Nur; Wati, Rianna (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to examine readers' receptions of the most popular stories in the Fizzo application. Reader reception is the reader's response or the reader's response to a literary work that is read. This research uses a qualitative descriptive approach. Data collection uses reading, listening, and recording techniques. The data source in this study is the comment column in the Fizzo Application on the most popular story entitled Dinikahi Gus Dingin by Hello Cutie The results showed that the story entitled Dinikahi Gus Dingin by Hello Cutie has many comments from readers. comments that vary greatly there are comments that mean dominant, comments that negotiate, and comments that are oppositional. The author hopes that this article will benefit readers and other researchers.